PENDAPAT HAKIM MENGENAI EFEKTIFITAS UNDANG-UNDANG NOMOR 16 TAHUN 2019 PASAL 7 TENTANG DISPENSASI NIKAH DI PENGADILAN AGAMA KABUPATEN MALANG KELAS 1A - Muhammad Fauzul Adhim; Ach. Faisol; Moh. Muslim (Jurnal Hikmatina, 2021)
This research explains the effectiveness of Law No. 16 of 2019 article 7 About marriage dispensation in The Religious Court of Malang District Class 1A and this research aims to find out how the application of Law No. 16 of 2019 article 7 about the dispensation of marriage and whether or not this Law has been effective. This study uses a qualitative research type with an empirical juridical approach. The results of the study showed that Law No. 16 of 2019 article 7 has not been effectively implemented due to the submission of marriage dispensation in the Religious Court of Malang District Class 1A increased after the enactment of Law No. 16 of 2019. The court has sought to enforce the law to the fullest extent possible to reject applications for marriage dispensation in trials and conduct regular socialization to the public every month in the hope of raising public awareness to comply with the rules and reduce the number of underage marriages.